Dose reduction using care dose4d technique of siemens dual-source computed tomography on pediatric congenital heart disease - Chen, HongYing (2022)
Congenital heart defects (CHD) are the most prevalent birth defects. It is very important to diagnose CHD early and accurately so that patients can get timely and effective treatment. CT scan can accurately evaluate the anatomical structure and major malformations of the cardiac great vessels, the adjacent relationship between the mediastinal organs and tissues from morphology, and quantitatively evaluate cardiac function. However, ionizing radiation is the biggest drawback in CT scanning. This research using a cross-sectional prospective study to investigate the value of Siemens dual-source Somatom Definition Flash CT scanner using CARE Dose4D technique in decreasing radiation dose and ensure image quality in pediatric CHD. There were two groups used Siemens dual-source Somatom Definition Flash CT scanner. The CARE Dose4D group (n=32) with CARE Dose4D technique with automatic modulated tube current and 80 kVp tube voltage, there were patients of angiography pulmonary and thorax CT scanning. Control group (n=42) (Data from previous research: Fan et al.,2020) using the retrospective electrocardiogram (ECG) triggered sequential technique with 100 mAs tube current and 70 kVp tube voltage. The volume CT dose index (CTDIvol) and dose length product (DLP) on each patient was recorded to calculate the effective dose (ED). Calculated image noise signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR). All images of 32 pediatric patients in the CARE Dose4D group were clear. The contrast medium density of superior vena cava was moderate, the CT values of all vessels were similar, and the contrast mediums in all atrioventricular and vascular were full, with clear boundaries, no effect on image reconstruction. The CNR values descending aorta of males was lower than females in CARE Dose4D group (P=0.022<0.05). According to the results of this study, we believe that CT examination combined with CARE Dose4D technology can be applied to CHD diagnosis, and the long-term monitoring of radiation dose is more important in practice. The X-ray radiation dose optimization of children and infants still needs in-depth research.